Sou Fujimoto - Pollock, Naomi R., 1971- (London : Phaidon, 2016)
Occasionally an architect emerges whose vision is so fresh that it causes us to reconsider the very nature of architecture. Sou Fujimoto is one of those architects. Guided by instinct and keen observation, he casts convention aside. Instead he blurs boundaries and routinely rethinks basic building blocks. Both comfortably familiar and curiously enigmatic, Fujimoto's dynamic work grabs our attention then lingers on in our minds. Born and bred in Hokkaido, Fujimoto received his undergraduate degree in architecture from Tokyo University before embarking on an uncharted, solo exploration that probed the possibilities of architecture. Unfettered by the ideas and practices of others, Fujimoto's work has clarity of thought and purity of execution seldom seen. Fujimoto garnered significant international attention for his popular 2013 Serpentine Pavilion in London (Fujimoto was the youngest architect to receive the highly-regarded commission). In 2012 he was part of the Japanese team that won a Golden Lion award for Best National Participation at the Venice Architecture Biennale for their design of alternative housing concepts for the homes that were destroyed by the tsunami.
Keywords: Architectuur ; toekomst